The Aesthetic-Poetic Translation Analysis on Toety Heraty’s Poetry Entitled ‘The Moon is High’ - Arini Sabrina; Ajar Pradika Ananta Tur (Universitas Tidar, 2023)
As several studies emerge analysing some literary work translation, there is lack of study focusing on such translation with certain point of view. This study then exists with the aim to qualitatively analyse Toety Heraty’s poetry entitled ‘The Moon is High’ translated by Carole Satyamurti, a British poet, with the aesthetic-poetic view. As the findings, it is concluded that, even though the translator employs some literal translations, but more often she implements aesthetic-poetic translation method to replicate the poetry along with retaining the poetic nuance from the word choices. However, it will be a challenge for whoever translating literary work with aesthetic-poetic translation method, since the transfer of the message will not only demand the lexical equivalence, but also the similar ‘beauty’ of the work.